Robust Optimization of Micro-Grid of Natural Gas and Renewable Energies Considering Operational Performances and Flexibility - Zhang, Tao (Frontiers in Energy Research, 2022)
The micro-grid based on renewable and fossil energies relieves environmental pollution due to fuel pollutant emission and offsets renewable energies' instabilities. A micro-grid integrated with wind, solar, and natural gas is proposed. Primary energy saving rate, annual total cost saving rate, and carbon dioxide emission reduction rate are employed to evaluate the energetic, economic, and environmental performances of micro-grid, and grid integration level and net interaction level between micro-grid and national grid are used to show its system operational flexibility. The multi-objective robust optimization model considering these indicators in non-dominated sorting genetic algorithm II is constructed, in which the linear regression models fitted using points in the neighborhood of each candidate solution are used to present sensitivity analysis for the selection process of optimal solutions. The simulations in a case study demonstrate the validation of the proposed optimization model. The results show that the primary energy saving rate, annual total cost-saving rate, and CO2 reduction rate are decreased by 1.7%, 19.8%, and 1.2%, respectively, when integrating system flexibility into optimization objectives.